Onontkoombaar verleden. Reflecties op een veranderende historische cultuur: Inescapable past: Reflections on a changing historical culture (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This collection of essays represents Maria Grever’s farewell to Erasmus University in Rotterdam, where she founded the renowned Centre for Historical Culture in 2006 and as whose professor she is now retiring. The collection is dedicated to the topic of “historical culture”, a multi-layered concept of which the author identifies three dimensions: 1. “the stories that people tell”; 2. “the formal and informal historical infrastructure” (such as schools, archives, museums); and 3. “conceptions of history”, linked to terms such as “progress”, “rise” and “fall”. Historical culture, properly understood as a holistic access to the past, encompasses “both academic and popular history, articulated in material and immaterial culture” (p. 8).
Keywords: Maria Grever; Onontkoombaar verleden; Reflecties op een veranderende historische cultuur; Inescapable past; Reflections on a changing historical culture